Mamdani fuzzy-based water quality monitoring and control system in vannamei shrimp farming using the internet of things - Qomaruddin, Muhammad; Riansyah, Andi; Hermawan, Hildan Mulyo (Institute of Advanced Engineering and Science, 2024)
Indonesia's vast ocean expanse, spanning two-thirds of its land, is a treasure trove of marine resources, with shrimp being a vital commodity in the country's fisheries exports. To ensure successful shrimp production, maintaining optimal water conditions is paramount, necessitating extensive, large-scale monitoring. Enter our innovative prototype an internet of things (IoT) system designed for comprehensive pond water quality oversight. This smart system monitors crucial parameters like pH, turbidity, temperature, and dissolved solids in vannamei shrimp cultivation. The Mamdani fuzzy approach dynamically adjusts operations in response to changing weather conditions, fine-tuning both pump and windmill speeds. This adaptive methodology significantly improves water quality control, enhancing overall efficiency. Our IoT infrastructure ensures real-time monitoring and control, creating an ideal environment for shrimp cultivation. The Mamdani fuzzy technique’s effectiveness shines in adapting to dynamic environmental shifts. Noteworthy findings underscore the system's ability to automate and elevate pond water quality, promising increased shrimp production. This technology has the potential to revolutionize traditional shrimp farming, particularly in regions like Rembang, by promoting sustainable aquaculture practices.